The Role of Social Cue Utilization and Closing-the-Loop Communication in the Performance of Ad Hoc Dyads. (September 2017) - Yee, Daniel J.; Wiggins, Mark W.; Searle, Ben J.
Objective: To examine whether social cue utilization impacts the performance of ad hoc dyads through its relationship with closing the loop, a communication process whereby team members respond more frequently to initiating statements made by others. Background: There lacks unequivocal experimental evidence for any single cognitive-based process that might predict the performance of ad hoc teams. Method: Using a quasi-experimental design, 80 participants were classified into 40 dyads based on their levels of social cue utilization and attempted a team problem-solving task. A serial mediation model revealed an indirect effect of social cue utilization on the performance of ad hoc dyads through closing the loop. Results: Analyses indicated that social cue utilization impacts on the performance of ad hoc dyads independently of nonverbal reasoning ability and emotional intelligence. Further, the level of social cue utilization within dyads exhibits a positive indirect impact on the performance of ad hoc dyads through closing the loop. Conclusion: Ad hoc dyads with higher levels of social cue utilization engaged in a greater frequency of closing-the-loop statements and showed better subsequent performance on a problem-solving task in comparison to dyads with lower levels of social cue utilization. Application: Potential applications include the optimization of ad hoc team composition within high reliability environments like aviation and power control as well as improving training interventions with a specific mechanism for improving the performance of ad hoc teams.